CLINICAL AND MORPHOMETRIC INDICES IN DOMESTIC CATS AND DOGS SUFFERING FROM OBESITY BECAUSE OF DIABETES - Lokes-Krupka, T. P.; Tsvilikhovsky, M. I. (Scientific Progress & Innovations, 2019)
Clinical, morphometric indices of domestic cats and dogs suffering from diabetes mellitus depending on type were determined and analyzed, as well as morphometric indices in case of obesity because of diabetes and the indices of patients with alimentary obesity were compared. The aim of the article is the comparative analysis of clinical signs in domestic cats and dogs in case of diabetes of different types, as well as the com-parison of morphometric parameters of animals with obesity resulting from diabetes with the obesity of ali-mentary origin. Breed and age disposition of domestic cats and dogs to diabetes, depending on its type was determined; it was found that Persian breed cats suffer from type I diabetes more often, while not thorough-bred cats suffer from type II diabetes. Among the reported cases of domestic dog diabetes mellitus, the pa-thology was most often recorded in dogs of the Labrador-retriever and poodle breeds. Analyzing the age-related dynamics of developing cat diabetes, we found that the largest number of animals with the specified pathology was detected in the age category of over 10 years. The next group was animals of 7-9 years old. Most often dog pathology on the background of obesity was recorded in animals older than 10. Concerning type 1 of the disease, domestic dogs aged seven years and older are susceptible to it. The main clinical signs of domestic dog and cat diabetes mellitus were: general weakness, suppression and worsening the coat of wool quality (caused by prolonged hyperglycemia and the development of intoxication due to metabolic dis-orders), as well as hypo- and anorexia. There was a significant similarity of morphometric parameters in both kinds of animals at alimentary and endogenous obesity. A considerable difference of morphometric in-dices at different types of diabetes mellitus was registered both in domestic cats and dogs. The content of adipose tissue in the body of cats with type 1diabetes was 3.1 times lower as compared with the animals suf-fering from type II diabetes, and in dogs the content of adipose tissue was 2.8 times lower. The body weight of domestic cats also reliably differed, so in animals suffering from type II diabetes it was 3.3 more than in animals with type 1diabetes. The obtained research data can be used for diagnosing obesity of different gen-esis by practicing doctors of veterinary medicine.